Perbandingan Ketelitian Koordinat 3-D Antara Hasil Pengolahan Data GNSS Menggunakan Perangkat Lunak Hi-Target Geomatics Office dengan Trimble Business Center - Wijonarko Wijonarko; Henri Kuncoro (Fakultas Teknik, 2023)
The Global Positioning System (GPS) data processing method is a key to obtaining the accuracy of the 3-D coordinates. Therefore, there is commercial software issued by tool vendors and can be accessed by users. Among the software are Hi-Target Geomatics Office (HGO) and Trimble Business Center (TBC). Both of these software can be used to process GPS data by post-processing and can be accessed by users. In this study, a comparison of the results of GPS data processing using the two software will be carried out by comparing the accuracy of each software for processing GPS data at baseline of 5 – 10 m and 5 – 20 km. The results of data processing that was carried out in this study found that GPS data processing using both software at a baseline of 5 – 10 m did not show significant differences with the two having a difference of 1 mm in each coordinate component. However, at 5 – 20 km baseline the results of GPS data processing using TBC are more accurate with a difference of -0.0050 m in Northing, -0.0800 m in Easting and -0.0550 m in Elevation compared to the actual coordinates. With these results, the TBC software is more recommended.